Can recovered road sweeping wastes provide a soil or soil amendment alternative? An investigation of temporal variability of physico-chemical parameters - Daniel Niepsch; Edward Randviir; Rebecca Murphy-Peers; Emma Coulthard; David Hackett; David McKendry; David Megson (Journal of Environmental Management, 2025)

Otolith and Genomic Data Reveal Temporal Insights Into Stocking Across a Large River Basin in a Mobile, Long‐Lived Australian Freshwater Fish Species - Katherine A. Harrisson; Luciano B. Beheregaray; Christopher M. Bice; Emily J. Booth; Chris J. Brauer; Gavin L. Butler; David Dawson; Olga Dudchenko; Benjamin G. Fanson; Graeme Hackett; Annique Harris; Matthew J. Jones; et al. (Molecular Ecology, 2025)
Freshwater ecosystems and their biota are under increasing pressure from anthropogenic stressors. In response to declining fish stocks, hatchery and stocking programmes are widely implemented as core components of restoration and management strategies, with positive outcomes for some wild populations. Despite this, stocking remains contentious due to potential genetic and ecological risks to wild populations. Monitoring and evaluation of stocking outcomes are critical to ensuring the long‐term sustainability of wild populations, but identification of stocked individuals post‐release remains a key challenge, particularly for mobile species. In this study, we combined otolith (natal origin and age) and genomic data to identify stocked individuals and evaluate the genetic implications of stocking for a culturally and socioeconomically important and mobile freshwater fish, golden perch Macquaria ambigua (family: Percichthyidae), across Australia's Murray–Darling Basin (MDB). We also generated a chromosome‐level genome assembly. Many close kin were detected across the MDB, increasing in prevalence over recent decades and mostly of hatchery origin. Rivers with many close kin were associated with low effective population sizes ( N e

Intestinal microbiota of Nearctic‐Neotropical migratory birds vary more over seasons and years than between host species - Heather R. Skeen; David E. Willard; Andrew W. Jones; Benjamin M. Winger; Ethan F. Gyllenhaal; Brian R. Tsuru; Shannon J. Hackett; John Novembre (Molecular Ecology, 2023)
Seasonal migration of Nearctic‐Neotropical passerine birds may have profound effects on the diversity and abundance of their host‐associated microbiota. Migratory birds experience seasonal change in environments and diets throughout the course of the annual cycle that, along with recurrent biological events such as reproduction, may significantly impact their microbiota. In this study, we characterize the intestinal microbiota of four closely related species of migratory Catharus thrushes at three time points of their migratory cycle: during spring migration, on the summer breeding territories and during fall migration. Using observations replicated over 3 years, we determined that microbial community diversity of Catharus thrushes was significantly different across distinct time periods of the annual cycle, whereas community composition was more similar within than across years. Elevated alpha diversity in the summer birds compared to either migratory period indicated that birds may harbour a reduced microbiota during active migration. We also found that community composition of the microbiota did not substantially differ between host species. Finally, we recovered two phyla, Cyanobacteria and Planctomycetota, which are not commonly described from birds, that were in relatively high abundance in specific years. This study contributes to our growing understanding of how microbiota in wild birds vary throughout disparate ecological conditions and reveals potential axes across which an animal's microbial flexibility adapts to variable environments and recurrent biological conditions throughout the annual cycle.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Impacts on the metabolome of down-regulating polyphenol oxidase in potato tubers - Louise Vida Traill Shepherd; Colin James Alexander; Christine Anne Hackett; Diane McRae; Julia Anne Sungurtas; Susan Ramsay Verrall; Jennifer Anne Morris; Peter Edward Hedley; David Rockhold; William Belknap; Howard Vivian Davies (Transgenic Research, 2015)

Cellular mechanisms mediating the anti-invasive properties of the ornithine decarboxylase inhibitor α-difluoromethylornithine (DFMO) in human breast cancer cells - Andrea Manni; Sharlene Washington; David Mauger; Deborah A. Hackett; Michael F. Verderame (Clinical & Experimental Metastasis, 2004)

Diversity and Complexity of Erysiphe graminis f.sp. hordei Collected from Barley Cultivar Mixtures or Barley Plots Treated with a Resistance Elicitor - Adrian C. Newton; Christine A. Hackett; David C. Guy (European Journal of Plant Pathology, 1998)

Spiroplasma Species, Groups, and Subgroups from North American Tabanidae - Robert F. Whitcomb; Frank E. French; Joseph G. Tully; Patricia Carle; Roberta Henegar; Kevin J. Hackett; Gail E. Gasparich; David L. Williamson (Current Microbiology, 1997)